Observasi layanan perbankan syariah untuk memenuhi kepuasan nasabah: Kegiatan Observasi Publik Relation Pelaksanaan Kegiatan Di KCP Malang Sutoyo - Janan, Akhmad Syifaul (Maliki Interdisciplinary Journal, 2024)
This research aims to determine Sharia banking services to its customers. The method is carried out by direct observation. Observation of activities with direct interaction with the community and good circles within the bank. The object of research is Bank Syariah Indonesia, Sutoyo Sub-Branch Office, Malang City. The results of this research indicate that Bank Syariah Indonesia, Sutoyo Sub-Branch Office, Malang City provides good banking services to its customers in accordance with sharia principles.